2021
DOI: 10.3389/fbioe.2021.628050
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Classification of Locomotion in Response to Task Complexity and Anticipatory State

Abstract: ObjectiveIntent recognition in lower-extremity assistive devices (e.g., prostheses and exoskeletons) is typically limited to either recognition of steady-state locomotion or changes of terrain (e.g., level ground to stair) occurring in a straight-line path and under anticipated condition. Stability is highly affected during non-steady changes of direction such as cuts especially when they are unanticipated, posing high risk of fall-related injuries. Here, we studied the influence of changes of direction and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Including additional sensors may increase the computational complexity, which may increase the runtime for predicting user intent. Conversely, too few sensors may inadequately capture the user’s intent during complex tasks or task transitions [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Including additional sensors may increase the computational complexity, which may increase the runtime for predicting user intent. Conversely, too few sensors may inadequately capture the user’s intent during complex tasks or task transitions [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the bidirectional LSTM resulted in a mean root mean squared error (RMSE) of 1.42–5.71°, the study was limited to level-ground walking and did not explore feature combinations to reduce the number of input signals [ 22 ]. Kazemimoghadam and Fey (2021) examined the effect of training task combinations for task recognition accuracy of transitions and found that including data of the target task in the training data enhanced the prediction accuracy on unanticipated locomotion tasks [ 17 ]. Mundt et al (2020) used an artificial neural network using IMU sensors to predict joint angles with a mean RMSE < 4.8° [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation